Pengaruh Kompensasi Dan Disiplin Kerja Terhadap Kinerja Karyawan Cahaya Nikmah Bakery Kota Samarinda - Nor Azizah (Lokawati : Jurnal Penelitian Manajemen dan Inovasi Riset, 2025)
This study aims to examine the influence of compensation and work discipline on employee performance at Cahaya Nikmah Bakery located in Samarinda City. More specifically, this study analyzes three main things: first, the influence of compensation on employee performance; second, the influence of work discipline on employee performance; and third, the simultaneous influence of compensation and work discipline on employee performance. This study was conducted on 40 permanent employees who work at Cahaya Nikmah Bakery as research subjects. The method used in this study is a quantitative approach, with data collection techniques through observation, interviews, and questionnaires. The collected data were then analyzed using multiple linear regression techniques to determine the relationship and influence between the variables studied. The results of the data analysis show that the calculated F value of 35.898 is greater than the F table of 2.87 at a significance level of 5%. In addition, the significance value of 0.000 is below the critical limit of 0.05. This indicates that there is a simultaneous significant influence between compensation and work discipline on employee performance at Cahaya Nikmah Bakery. In other words, the combination of the two independent variables has a real contribution in influencing the level of employee performance. In addition to the simultaneous effect, the partial test results also show that each variable, namely compensation and work discipline, has a significant influence on individual employee performance. This is evidenced by the significance value for both variables, which is 0.000, which is also less than 0.05. The conclusion of this study shows that adequate compensation and the implementation of good work discipline can significantly improve employee performance. Therefore, company management is advised to continue developing a fair compensation system and strengthening a culture of work discipline to support overall company productivity and efficiency.